Analysing the role of the perceptual dimension in the formation of the urban third place - Joshi, Upendra; Nagarsheth, Snehal (Enquiry The ARCC Journal for Architectural Research, 2024)
Urban third places like parks, plazas, and cafes play a significant role in fostering social interaction, community engagement, and a sense of belonging in contemporary society, and this recognition is growing. It has been a subject of critical analysis across multiple disciplines and intellectual traditions. Although the term 'Third Place' has been the subject of considerable research for some time, a sensible investigation into the psychological needs of users broadens the study's scope, adding a new dimension to the research. This study's perceptual dimension focuses particularly on an individual's perceptions of the built environment of the urban third place. It deals with how people perceive and experience these places. Thus, the purpose of this paper is to investigate the contribution of the perceptions that users generate in the formation of urban third places. Research begins with an understanding of this term and its significance in an urban environment. The theoretical approach interprets a perceptual dimension by analysing an individual's 'Sense of Place' in relation to the urban third place. A projective survey questionnaire further explores the concept. We decipher the qualitative observations of the survey using Nvivo, a software tool that supports both descriptive and inferential statistical inferences. The consideration of age versus the diverse perceptual needs of the users explains the interrelationship while making it convenient for the statistical analysis of the study's observations. As a result, this research examines the significance of associations, identifies dominant perceptions, and analyses the possible patterns of the same across the identified age groups of the sample population. A statistical analysis of these observations offers insights to designers, planners, and policymakers in terms of prioritising users' experiences, needs, and preferences, i.e., sense of place, to accommodate the contemporary needs of the users in the practice of urban design at the human scale.